Human–AI Collaboration Reshaping Creative Labor and Professional Identity Dynamics - Galih (Manexia: Journal of Business, Management, and Creative Economy, 2026)
Creativity is increasingly no longer an exclusively human endeavor, as artificial intelligence becomes deeply embedded in processes of ideation, production, and evaluation. This shift challenges established assumptions about authorship, originality, and professional identity within the creative economy. Despite growing research on digital labor, artificial intelligence, and identity work, these domains remain theoretically fragmented, limiting understanding of how human–AI collaboration reshapes both creative processes and identity construction. This study addresses this gap by developing an integrative conceptual framework that bridges creative labor theory, identity work, and socio-technical perspectives. Using a mechanism-based analytical approach, the study conceptualizes creative labor as a hybrid co-creative system characterized by generative expansion, iterative co-creation, algorithmic mediation, and human curation. It further explains how these processes trigger identity transformation through recursive stages of destabilization, experimentation, negotiation, and reconstruction. The study contributes by reframing creativity as a distributed process, extending identity theory to incorporate AI as an active participant, and introducing the concept of hybrid intelligent labor, offering a foundation for future empirical inquiry.